2007
DOI: 10.1002/pits.20214
|View full text |Cite
|
Sign up to set email alerts
|

Language preference and its relationship with reading skills in English and Spanish

Abstract: A dearth of research has investigated the language preference of bilingual childhood populations and its subsequent relationship to reading skills. The current study evaluated how a sequential bilingual student's choice of language, in a particular environmental context, predicted reading ability in English and Spanish. The participants were Latino children ranging in age from 7 years, 5 months, to 11 years, 6 months, with 43% born in the United States. Results showed a relationship between a child's higher En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Spanish-speaking families likely mix their use of Spanish and English in different situations and with different people (Brenneman et al, 2007;Duursma et al, 2007). Overall language use in a home could range from exclusive use of Spanish, through varying degrees of mixed use, to exclusive use of English.…”
Section: The Interpersonal Context In the Home Is Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Spanish-speaking families likely mix their use of Spanish and English in different situations and with different people (Brenneman et al, 2007;Duursma et al, 2007). Overall language use in a home could range from exclusive use of Spanish, through varying degrees of mixed use, to exclusive use of English.…”
Section: The Interpersonal Context In the Home Is Complexmentioning
confidence: 99%
“…The Brenneman et al (2007) study included only items for the child's spoken language, not the lan-' The survey also included 13 activity items, including language for reading, activity frequencies, and number of books in the home.…”
Section: What We Know About the Nature Of Home Language Usementioning
confidence: 99%
“…The findings of this study confirmed the research hypothesis concerning a desire to return to the country of birth as a function of preference in using native language in a survey. This was expected because language preference is the primary indicator of acculturation (Clement, 1986; Kenney, 2002; Shahim, 2007) and is also associated with language proficiency (Brenneman, Moris, and Israelian, 2007; Chesterfield, Chesterfield, and Chavez, 1982) and ethnic identity (Lanca, et al, 1994; Noel, Pon and Clement, 1996; Romero et al, 2004; Shahim, 2007). Our findings are in agreement with the report that maintenance of the native language is essential for maintaining ethnic identity and cultural values (Shibata, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that proficiency in the language of the host country facilitates communication and interpersonal relationships. It has been shown that language preference and language proficiency are closely associated among immigrants (Brenneman, Morris, and Israelian, 2007; Chesterfield, Chesterfiled, and Chavez, 1982). Also, preference to use English language among immigrants predicted their social and cultural integration (Remennick, 2004).…”
Section: Language Acquisition Language Preference and Acculturationmentioning
confidence: 99%
“…Several studies have used the frequency of use in each language to establish dominance (Mayer-Crittenden et al 2014;Pearson, Fernandez, and Oller 1993;Pearson et al 1997). Brenneman, Morris, and Israelian (2007) as well as Fritz (2011), on the other hand, used the child's preferred language as evidence of language dominance. In Northern Ontario, a recent study identified children as being monolingual (French only) when they were exposed to less than five hours of input in their second language (English) and francodominant (mainly French speaking) if they were exposed to 24.4 hours per week in their second language (English).…”
Section: Procedure Test Scoring and Interpretationmentioning
confidence: 99%